SISTEM MANAJEMEN SURAT BERBASIS WEB DI STMIK KOMPUTAMA MAJENANG - Riswanto, Beny; Faisal Putra, Rahardika (Jurnal Teknologi dan Bisnis, 2021)
In the agency administration, the letter is an important means. Important information related to the agency and the secret is embodied in it . The timeliness of receipt of both outgoing and incoming mail should also be considered, therefore the management of incoming and outgoing mail must be implemented correctly. At this time, the procedure is applied to the management of incoming and outgoing mail to the Division of Administration of the STMIK Komputama Majenang from receipt, manufacture, storage, documentation, to verify the letter, all done conventionally. Documentation of incoming and outgoing mail only in the form of writing in the ledger. While on the stage of filing a letter only a hardcopy document storage. The Administration of STMIK Komputama Majenang felt the need to change the mail management method they are currently using, into a computerized and automated mail management method. With the Incoming and Outgoing Mail Management Information System, it is expected to be able to manage incoming and outgoing mail according to the specified flow, and can solve current problems. The filing of letters is done electronically, namely the storage of softcopy documents, and is equipped with reports of incoming and outgoing letters both daily and per period. In addition, this application also helps monitor the disposition of letters at the verification stage. The research methods used to solve various problems that occur are literature, observation, interviews, data and system analysis, system design, program development, program testing, program implementation. The result of this research is to produce an application that can manage incoming and outgoing mail according to the specified flow, and can solve current problems.